[LB.02.17]OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY AND ARTERIAL HYPERTENSION: A ROLE IN IDENTIFYING EARLY VASCULAR DAMAGE?. (September 2017) - Grossi, A.; Agostinis, M.; Moretti, S.; Tandurella, N.; Cavallaro, G.; Pierobon, V.; Tavecchia, L.; Mancuso, V.; Lippi, A.; Mongiardi, C.; Montalbetti, L.; Donati, S.; et al.
Abstract : Objective: Optical coherence tomography angiography (OCTA) is a novel, non-invasive OCT technique able to identify and characterize retinal vascular patterns. Aim of our cross-sectional study was to evaluate the correlation between retinal microvascular modifications detected with OCTA and arterial hypertension (AH). We also evaluated the role of OCTA as an useful tool for early diagnosis of subclinical organ damage in hypertensive patients. Design and method: We enrolled 70 subjects: 35 hypertensive and 35 normotensive (NT) patients matched for age, sex and BMI. Hypertensive patients was divided into two groups: mild (Blood Pressure-BP < 160/100 mmHg MH) and severe (BP >180/110 mmHg, SH). OCTA was performed applying different analysis protocols for macula and optic disk, using SD-OCTA Avanti Optovue by SSADA algorithm. OCT angiograms were studied with corresponding OCT B scans and retinal maps, to assess accuracy and clinical utility. Morphological data were correlated to office BP (OBP), central systolic blood pressure (c-SBP) and microalbuminuria (MI) to evaluate the predictive value of OCT analysis. Results: We observed a lower mean foveal choroidal thickness in hypertensive patients vs normotensive (NT 319, 68 ± 61, 72 mm, MH 251, 04 ± 63, 1 mm SH 262, 65 ± 51, 08 mm p = 0.003). Deep vascular layer resulted similar in the three groups (NT: 59, 2 ± 1, 5%; MH: 59, 2 ± 2.2%; SH: 57, 8 ± 2, 6%) as well as deep foveal avascular zone area (NT: 0, 34 ± 0, 09 mm 2 ; MH 0, 36 ± 0, 07 mm 2 ; SH: 0, 39 ± 0, 1 mm 2 ). Our preliminary data didn't show a significant correlation between morphological retinal parameters and OBP, c-SBP and microalbuminuria. Conclusions: Our data show how OCTA could highlight some vascular modifications in hypertensive patients, suggesting a potential usefulness of OCTA to assess ocular damage. We need largest studies to estabilish a predictive role of this technique.